Asset Management within Commercial Banking Groups: International Evidence - FERREIRA, MIGUEL A.; MATOS, PEDRO; PIRES, PEDRO (Journal of Finance, 2018)
ABSTRACT We study the performance of equity mutual funds run by asset management divisions of commercial banking groups using a worldwide sample. We show that bank‐affiliated funds underperform unaffiliated funds by 92 basis points per year. Consistent with conflicts of interest, the underperformance is more pronounced among those affiliated funds that overweight the stock of the bank's lending clients to a great extent. Divestitures of asset management divisions by banking groups support a causal interpretation of the results. Our findings suggest that affiliated fund managers support their lending divisions’ operations to reduce career concerns at the expense of fund investors.